A Critical and Textual Discourse Analysis of Beauty Product Advertisements - Hasan, Mahasin Abdulqadir (Arab Journal for Sciences and Research Publishing, 2022)
This research analyses the discourse of advertisement in different websites on beauty products depending of a linguistic model and a multi-model analysis to go behind what lies after the advertisement. The data of this research are quoted from different websites and channels and they will be limited to some advertisements. The results of the analysis show that most of the beauty product advertisements depend on a limited number of words rather than sentences, using affective colors, and famous celebrities as a way for attracting the audience. Another result is those using women’s pictures for showing not only the feministic features and tenderness, but women’s strength and challenge were also revealed.